An Islamic Framework for Character Education and Bullying Prevention: Integrating Aqidah, Akhlak, and Multiculturalism into Learning - Mappanyompa, Mappanyompa; Saprun, Saprun; Aqodiah, Aqodiah; Sahwan, Sahwan; Affandi, Shabibah Binti Shaufit (Universitas Muhammadiyah Surakarta, 2026)
Islamic Religious Education in preventing and dealing with bullying behavior has a very important role, in creating a harmonious and noble social environment at various levels of education. However, there is a lack of studies that integrate Islamic values in religious education that specifically address the issue of bullying. Therefore, this study aims to investigate how the reformulation of Islamic Religious Education can foster a bullying-free campus culture. This research method is qualitative field research, where data is obtained directly using observation, interviews, and documentation. The collected data were analyzed using the Miles and Huberman model interactive analysis technique which includes data reduction, data presentation, and data verification and conclusions. The results of this study show that the reformulation of Islamic Religious Education materials that integrate Aqidah, morals, and multicultural values through the approach of the Qur'an, hadith, Prophetic practices, and tarikh material, accompanied by learning methods that recognize student personalities based on culturais backgrounds, and inclusive class organization, significantly contribute to preventing bullying. This integration instills the values of equality, empathy, and respect for diversity, thus creating a humane, tolerant, and discrimination-free academic environment. Thus, it is hoped that the results of this research can provide solutions in overcoming the issue of bullying in higher education through the reformulation of Islamic Religious Education that integrates aqidah, akhlak, and multicultural values. This is important to create an academic environment that is inclusive, harmonious, and based on Islamic values.